2023
DOI: 10.3390/catal13010113
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Valorization into Methane Using Samarium Oxide-Supported Monometallic and Bimetallic Catalysts

Abstract: Samarium oxide (Sm2O3) is a versatile surface for CO2 and H2 interaction and conversion. Samarium oxide-supported Ni, samarium oxide-supported Co-Ni, and samarium oxide-supported Ru-Ni catalysts were tested for CO2 methanation and were characterized by X-ray diffraction, nitrogen physisorption, infrared spectroscopy, H2-temperature programmed reduction, and X-ray photoelectron spectroscopy. Limited H2 dissociation and widely available surface carbonate and formate species over 20 wt.% Ni, dispersed over Sm2O3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
3
6
0
Order By: Relevance
“…On the XRD data of the reduced catalysts (Figure ), the diffraction peaks at 24, 28, 31.5, 34, 41, 50, and 55.5° correspond to ZrO 2 (ref 00-065-0728), while those at around 44, 51, and 75° are attributable to metallic Ni 0 (ref 01-077-9326) for all catalysts. On the calcined samples (data not shown), peaks characteristic of NiO were observed at 37 and 43°, similar to previous findings . The absence of these peaks on the reduced samples (Figure ) confirms the complete reduction of NiO to metallic Ni 0 .…”
Section: Results and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the XRD data of the reduced catalysts (Figure ), the diffraction peaks at 24, 28, 31.5, 34, 41, 50, and 55.5° correspond to ZrO 2 (ref 00-065-0728), while those at around 44, 51, and 75° are attributable to metallic Ni 0 (ref 01-077-9326) for all catalysts. On the calcined samples (data not shown), peaks characteristic of NiO were observed at 37 and 43°, similar to previous findings . The absence of these peaks on the reduced samples (Figure ) confirms the complete reduction of NiO to metallic Ni 0 .…”
Section: Results and Discussionsupporting
confidence: 89%
“…On Ni-based catalysts, it is commonly reported that Ni 0 sites in their metallic state are the active sites for CO 2 methanation . This is confirmed by the absence of any catalytic activity on blank tests using solely the bare supports, as will also be elaborated later in this work, validating the essential need of Ni 0 active sites for the reaction.…”
Section: Results and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…8,12 In terms of promoters' nature, rare-earth metal oxides such as CeO 2 , La 2 O 3 , Sm 2 O 3 , and Y 2 O 3 have been the ones most commonly studied. 7,8,12,13 Concerning the supports, metal oxides such as Al 2 O 3 , SiO 2 , CeO 2 , TiO 2 , and ZrO 2 , among others, have been reported. 7 In addition, micro-and mesoporous materials such as zeolites 14 or carbons 7,15−19 have been the focus of recent studies, revealing promising results.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of active metal nature, transition (e.g., Ni, Co) and noble (e.g., Ru, Rh) metals have been reported. , Considering their price and availability, Ni-based catalysts have been the ones most studied and used in CO and CO 2 methanation. , However, they suffer from the fast deactivation caused by several factors such as sintering, reoxidation, or even coke deposition . To overcome this, the incorporation of promoters, tuning of the metal-support interactions, or improvement of the synthesis method, among all, were found to play a crucial role. , In terms of promoters’ nature, rare-earth metal oxides such as CeO 2 , La 2 O 3 , Sm 2 O 3 , and Y 2 O 3 have been the ones most commonly studied. ,,, Concerning the supports, metal oxides such as Al 2 O 3 , SiO 2 , CeO 2 , TiO 2 , and ZrO 2 , among others, have been reported . In addition, micro- and mesoporous materials such as zeolites or carbons , have been the focus of recent studies, revealing promising results.…”
Section: Introductionmentioning
confidence: 99%